Personal Values and Cultural Resilience in Ziarah: Toward a Model of Sustainable Pilgrimage Culture in Indonesia - Muhammad Naqib Abdullah; Thomas Stefanus Kaihatu (KURAS Institute, 2025)
This study examines pilgrimage (ziarah) to the tomb of KH. Abdurrahman Wahid (Gus Dur) as an adaptive and resilient cultural system within contemporary Indonesian Islam. Rather than treating pilgrimage solely as a religious rite or a form of religious tourism, it conceptualizes ziarah as a socio-cultural ecosystem shaped by ongoing negotiations among individual values, collective meanings, and material structures. The analytical framework integrates Schwartz’s Basic Human Values Theory and Ungar’s Cultural Resilience Theory to bridge micro- and macro-level analysis. Methodologically, the study adopts a qualitative multi-method approach based on secondary data analysis, including statistical data, surveys of pilgrims’ motivations, ethnographic findings, and analyses of media and community narratives. The findings indicate that pilgrims’ motivations are diverse and overlapping, driven by distinct configurations of psychological values, which are articulated into four dominant pilgrim archetypes—Ritualists, Moralists, Seekers, and Tourists—coexisting within a single pilgrimage ecosystem. The cultural resilience of the Gus Dur pilgrimage site lies in its capacity to accommodate these archetypes without compromising its spiritual core, mediated by Gus Dur’s role as a central figure with religious, political, and moral legitimacy and reinforced by the transformation of pilgrimage into a community-based socio-economic ecosystem. As a synthesis, the study proposes a Sustainable Pilgrimage Culture Model that offers theoretical and practical contributions to inclusive, value-centered, and sustainable pilgrimage governance.